Comparative study of oral lipid nanoparticle formulations (LNFs) for chemical stabilization of antitubercular drugs: physicochemical and cellular evaluation. (31st October 2018) - Banerjee, Subham; Roy, Subhadeep; Nath Bhaumik, Kaushik; Kshetrapal, Pallavi; Pillai, Jonathan
Abstract: Rifampicin (RIF) and Isoniazid (INH) are two major first-line antitubercular drugs (ATDs) that are typically administered orally, in combination. However, INH-catalysed degradation of RIF under acidic pH environment of the stomach is a major concern related to its oral delivery, and is dramatically accelerated upon further exposure to and interaction with INH. This interaction, in turn, triggers a direct decline in the available RIF dose below the sub-therapeutic level, thereby diminishing its therapeutic efficacy. We hypothesized that encapsulation of both these important ATDs into lipid nanoparticle formulations (LNFs) may help mitigate the acid hydrolysis of RIF, its subsequent interaction with INH and its eventual INH-mediated accelerated chemical degradation in the gastric environment. We further hypothesized that these LNFs would be capable of enhanced uptake and localization into intra-cellular compartments of lung macrophages, thereby potentially targeting the Tb pathogen in its in vivo niche. For this purpose, we evaluated two promising LNFs, viz., solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) for encapsulating these ATDs. Here, we report on the design, development and comparative evaluation of SLN and NLC-based lipid formulations of both INH and RIF. Our strategy of nanoencapsulation substantially prolonged encapsulated RIF release and improved its chemical stability in presence of INH in a simulated gastric acidic environment. In vitro cell culture studies showed a well-quantifiable uptake of LNFs in a human alveolar macrophage cell line. Overall, these evaluations provided promising results for establishing the potential of both formulations for TB therapy.